PERANCANGAN DAN ANALISIS STATIS BAN TANPA UDARA (AIRLESS TIRE) UNTUK UKURAN 165/60 R12 - Sandya Gilang Samudra; Mohamad Yamin (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2021)
Electric cars have large torque from the start driven or acceleration. The use of conventional tires on electric cars can accelerate tire surface wear. Airless tires can be applied to electric cars, such as those being developed by the Bridgestone and Micheline tire companies. This research was conducted to determine, predict stress, displacement, strain and safety factor values and evaluate the design results through FEA simulations of the airless tire model. The contribution to be achieved in this research is to redesign to improve the stress, displacement, strain and safety factor of the airless tire model that has been previously studied. In this study, airless tire planned with size 165/60 R12 refers to the ETRTO standard. The airless tire model is visualized using the AutoCAD and CATIA software. The FEA (Finite Element Analysis) simulation is done with SOLIDWORKS. The honeycomb structure uses polyurethane as the main honeycomb component suitable for pneumatic tire replacement. The 4 planned honeycomb models show better stress, displacement, strain and safety factors compared to the comparative airless tire model previously examined.